2012
DOI: 10.1152/ajpcell.00305.2011
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and voluntary exercise together promote quadriceps hypertrophy and increase vascular density in female 18-mo-old mice

Abstract: Age-related sarcopenia reduces the size, strength, and function of muscle, and the diameter of muscle fibers. It also disrupts the dystrophin-glycoprotein complex, dislocating nitric oxide synthase 1 (NOS-1) and reducing sarcolemmal integrity. This study of quadriceps muscle in 18-mo-old mice showed that NO-donor treatment with isosorbide dinitrate (I) for 6 wk, in combination with voluntary exercise for 3 wk, increased muscle mass by 25% and stimulated cell proliferation. The resulting fiber hypertrophy was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 85 publications
2
53
1
Order By: Relevance
“…As indicated by previous studies (Leiter and others 2012; Rice and others 2006) and suggested by our DGC findings, sarcolemmal damage occurs with sedentary, ad libitum aging. To examine this further, we investigated how aging as well as lifelong diet and exercise interventions, on membrane-repair machinery in aged muscle fibers.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As indicated by previous studies (Leiter and others 2012; Rice and others 2006) and suggested by our DGC findings, sarcolemmal damage occurs with sedentary, ad libitum aging. To examine this further, we investigated how aging as well as lifelong diet and exercise interventions, on membrane-repair machinery in aged muscle fibers.…”
Section: Resultssupporting
confidence: 89%
“…Lieter et al (2012) found that cytoplasmic localization of nNOS is greater in quadriceps of 19.5 month old mice vs. young mice, which could exacerbate proteolysis and atrophy (Suzuki and others 2007). However, 6 weeks of administration of an NO-donor drug and 3 weeks of exercise in 18 month old mice prevented mislocalization of nNOS, concomitant with muscle hypertrophy (Leiter and others 2012). Consistently, loss of sarcolemmal nNOS was causal in skeletal muscle fiber cross-sectional area during disuse (Lawler and others 2014; Suzuki and others 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This is seen as particularly important in determining the potential role of SC behavior in defining the capacity for fiber growth by hyperplasia and hypertrophy in zebrafish versus its restriction to fiber hypertrophy in other taxa such as the mouse. In mouse muscle, such interplay affects development and disease progression, the scope of SC heterogeneity, and growth and regenerative capacity (Janke et al, 2013;Leiter and Anderson, 2010;Leiter et al, 2012). Fiber-type specific differences in the NO-HGF-c-met signaling pathway may also be revealed by future studies on fibers, as muscle growth and power are so highly dependent on fast-twitch fibers in fish.…”
Section: Research Articlementioning
confidence: 99%
“…On the other hand, NO exerts several distinct effects on various aspects of skeletal muscle structure and function that could possibly be favourable in strength/power sports, such as excitation-contraction coupling [9], skeletal muscle fiber type conversion (faster-to-slower fiber type) [10], modulation of mitochondrial energy production [11] and glucose metabolism [12]. Further, animal studies provided evidence that nitric oxide may promote exercise-induced muscle hypertrophy [14,[46][47][48], stretch-induced proliferation of myoblasts [49] and prevent muscle atrophy [50]. Indeed, Gomez-Gallego et al [31] proposed that the association of T-786C polymorphism with elite power status may be attributed, at least in part, to the role that NO plays on muscle hypertrophy.…”
Section: Sub-elite); N -The Number Of Athletesmentioning
confidence: 99%